2003
DOI: 10.1016/s1010-7940(03)00465-2
|View full text |Cite
|
Sign up to set email alerts
|

Repair of post-infarct ventricular septal defect with or without coronary artery bypass grafting in the northwest of England: a 5-year multi-institutional experience

Abstract: These data provide evidence that concomitant CABG is significantly beneficial to mid-term mortality rates. We recommend that patients who present with post MI VSD who have multivessel disease should be routinely revascularised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
4
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 23 publications
4
71
4
4
Order By: Relevance
“…This difference was close to statistical significance: p = 0.059 with Fisher's exact test. Our total percentage of residual shunt is similar to the 24% of Barker et al [21], who used mixed techniques as we did. Other authors reported figures as high as 43% [7].…”
Section: Discussionsupporting
confidence: 88%
“…This difference was close to statistical significance: p = 0.059 with Fisher's exact test. Our total percentage of residual shunt is similar to the 24% of Barker et al [21], who used mixed techniques as we did. Other authors reported figures as high as 43% [7].…”
Section: Discussionsupporting
confidence: 88%
“…4 This introduces a significant selection bias into surgical series, artificially inflating survival rates. [5][6][7][8] The advent of the Amplatzer family of ventricular septal defect (VSD) closure devices offers a potentially attractive alternative to surgical repair with multiple device implants possible if required ( Figure 1A). A few series of selected cases exist, with good results reported, [9][10][11] but there are no large series with early as well as delayed intervention.…”
mentioning
confidence: 99%
“…По дан-ным литературы госпитальная летальность при хирурги-ческом закрытии дефекта составляет 23-81% [2,15,16]. Высокая летальность после подобных операций обус-ловлена исходной тяжестью оперируемых больных, пожилым возрастом пациентов, тяжелой сопутствую-щей патологией, а также нередкими техническими про-блемами хирургической процедуры [17].…”
Section: Discussionunclassified